Conference 2017: From Innovation to Patient Solution. An international symposium held jointly by CSPS and CC-CRS, May 10-12, 2017, Montréal, QC Canada - . . (Frontiers Media S.A., 2017)
Plenaries and Special Presentations: Bettina Hamelin, NSERC: Positioning Canada to Lead: Come Together, Right Now! Frank Béraud, CEO, Montréal InVivo: Competitiveness of Quebec Life Sciences: How do we Compare to the Best? Jason Moffat, University of Toronto: Genome-scale CRISPR Screens and Protein Engineering for Target Discovery and Translation Marcel Bally, BC Cancer Agency - CSPS Leadership Award: Lipids, Drugs and Metals: Ingredients for Promising Anticancer Drugs Mohsen Sadatsafavi, University of British Columbia - GSK Early Career Award Lecture: Respiratory Evaluation Sciences Program (RESP): Innovations in Analytic Approaches to Improve Efficiency in Respiratory Care Conference Sessions: Special Session: Innovation and Development of Modern Pharmaceuticals 1. Immuno-Oncology 2. Crossing Biological Barriers 3. Translational Medicine 4. Key Regulatory Issues 5. What is Happening in Antibacterials? 6. Gene Therapy 7. Biosimilars 8. Orphan Diseases